CURRENT WAGE AND LABOR REGULATION PROBLEMS IN RUSSIAN RESTRAURANTS END HOTELS - E. Sh. Kachalova (Модернизация, инновация, развитие, 2016)
At present, considerable disproportions take place in Russia between organizational, regulatory, social and economic relations actually existing in restaurant and hotel business enterprises on one part and provisions of their legal law basic norms and regulations on the other part. Labor organization and normative practice improvement directions are proposed for enterprises of the branch. Economic essence of the “tipping” phenomenon is revealed. Measures aimed at elimination of overcoming wage rise rates in comparison with those of the labor productivity presently existing in the branch.